2017
DOI: 10.1097/sla.0000000000001884
|View full text |Cite
|
Sign up to set email alerts
|

Suicide, Self-harm, and Depression After Gastric Bypass Surgery

Abstract: The increased risk of post-surgery self-harm and hospitalization for depression is mainly attributable to patients who have a diagnosis of self-harm or depression before surgery. Raised awareness is needed to identify vulnerable patients with history of self-harm or depression, which may be in need of psychiatric support after GBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 41 publications
4
71
0
4
Order By: Relevance
“…In this study, patient discussions about reviews by the surgeon were in reference to band management. Recent studies have reported that patients undergoing bariatric surgery were at increased risk of suicide and self‐harm . The unique GP–patient relationship may be pivotal in identifying patients at an increased risk of experiencing psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, patient discussions about reviews by the surgeon were in reference to band management. Recent studies have reported that patients undergoing bariatric surgery were at increased risk of suicide and self‐harm . The unique GP–patient relationship may be pivotal in identifying patients at an increased risk of experiencing psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…5-7 Recent populationbased observational studies have identified an increased risk of suicide and self-harm among patients who underwent surgery, compared to non-surgically treated individuals and the general population.Moreover, longitudinal studies have demonstrated that the risk of self-harm increases following treatment in those patients who choose to undergo surgery. [8][9][10][11][12] Despite these reports, there is sparse evidence from randomized trials assessing the risk of suicidality and self-harm following bariatric Alejandro Szmulewicz, Kerollos N. Wanis and Ashley Gripper contributed equally to this work.…”
mentioning
confidence: 99%
“…However, recent advancements within this complex topic yielded rather heterogeneous results. Lagerros et al (2016) examined self-harm diagnoses and completed suicides in a recent patient register-based Swedish study comprising over 22,000 gastric bypass patients. The authors reported an increase in self-harm diagnosis from 0.38 per 100 person-years before to 0.59 per 100 person-years two years after surgery.…”
Section: Self-harm and Suicidalitymentioning
confidence: 99%